2020
DOI: 10.1111/ijcp.13917
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy of the COVID‐19 by health care personnel

Abstract: Background The determination of the acceptance of the COVID‐19 vaccine by the health personnel will also be a guide for the upcoming vaccination studies. The aim of this study is to determine the acceptance status of COVID‐19 vaccine amongst healthcare professionals. Materials and methods A total of 1138 healthcare workers participated in this cross‐sectional study between 17th and 20th of September, 2020. The questionnaire, which was delivered via social media, was fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
128
5
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(167 citation statements)
references
References 7 publications
16
128
5
13
Order By: Relevance
“…The study revealed high vaccine acceptance among healthcare professionals working in Afghanistan (72.0%) and Libya (70.0%). This can be compared to a study in Turkey, where 68.8% of the healthcare worker are willing to take the COVID-19 vaccine (Kose et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed high vaccine acceptance among healthcare professionals working in Afghanistan (72.0%) and Libya (70.0%). This can be compared to a study in Turkey, where 68.8% of the healthcare worker are willing to take the COVID-19 vaccine (Kose et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Eine Befragung von 1138 türkischen HCWs im September 2020 ergab eine Impfbereitschaft gegen SARS-CoV-2 von 69 % [17]. Zwischen März und Juli 2020 wurden 1554 französische HCWs befragt, dabei votierten 77 % für eine Impfung [10].…”
Section: Auswahl Eines Bestimmten Impfstoffsunclassified
“…Studien aus China und der Türkei berichten von einer Bereitschaft zur SARS-CoV-2-Impfung unter Angestellten im Gesundheitswesen von ca. 70 % [18,19] und in Frankreich von 76,9 % [20]. Der Anteil der impfbereiten Augenärzte in unserer Studie ist somit vergleichsweise hoch.…”
Section: Impfbereitschaft Im Gesundheitswesenunclassified
“…Der Anteil der impfbereiten Augenärzte in unserer Studie ist somit vergleichsweise hoch. Wie in der Allgemeinbevölkerung (s. oben) wird in Publikationen aus Israel, der Türkei, USA und China eine Abhängigkeit der Impfbereitschaft bei Angestellten im Gesundheitswesen von Alter und Geschlecht beschrieben, außerdem aber auch von der Berufsgruppe (Ärzte, Pflege, Auszubildende, Sonstige), von der jeweiligen medizinischen Fachrichtung und von der direkten Arbeit mit COVID-19-positiven Patienten oder der subjektiven Risikobewertung [18][19][20][21][22]. Tendenziell würden sich in Umfragen unter Angestellten im Gesundheitssektor Männer, ältere Personen und Personen, die das persönliche Risiko z.…”
Section: Impfbereitschaft Im Gesundheitswesenunclassified